Time reduction effects of steel connected precast concrete components for heavily loaded long-span buildings - Lee, Ho-Haeng; Kim, Ki-Ho; Son, Seunghyun; Park, Kwangheon; Kim, Sunkuk (Journal of Civil Engineering and Management, 2020)
The characteristics of large logistics buildings are their long spans and the ability to take heavy loads. Usually, PC components are used for their frames to ensure quick construction. However, the erection of most pin jointed PC structures increases the time and the cost incurred for ensuring structural stability and construction safety. To solve this problem, “smart” frames have been developed, which have tapered steel joints at both ends of the PC components. A smart frame with the moment frame concept not only assures structural stability and construction safety, but it also simplifies and quickens the erection because of its tapered joint detail. The purpose of this study is to compare the erection time and cost effects of the steel connected PC components for heavily loaded long-span logistics buildings with the existing PC frames. For this study, we selected a logistics building constructed with PC components and redesigned it as the smart frame, and the erection simulations were performed. We analyzed the time reduction effects of the smart frame. Our results confirmed that the use of the smart frame reduced the erection time and cost practically. Our investigations will help develop the erection simulation algorithms for smart frames.